Using digital analytic tools for the purpose of marketing and selling products and services of ecommerce-integrated companies - Nguyen, Minh Ngọc (H. : ĐHQGHN, 2020)
Summary of the findings of the thesis: - The popular digital analytics tools: Google Analytics, Facebook Insight Tools. - Factors that affect decision: Analytics / Software Knowledge, Human Resources, Ease of Setup & Use, staff Expertise, Data Visualization, Budget, Advantages of the tools.